Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/s13028-014-0049-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular changes after administration of aerosolized salbutamol in horses: five cases

Abstract: Prevention and treatment of intraoperative hypoxemia in horses is difficult and both efficacy and safety of therapeutic maneuvers have to be taken into account. Inhaled salbutamol has been suggested as treatment of hypoxia in horses during general anesthesia, due to safety and ease of the technique. The present report describes the occurrence of clinically relevant unwanted cardiovascular effects (i.e. tachycardia and blood pressure modifications) in 5 horses undergoing general anesthesia in dorsal recumbency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…In horses the risk of occurrence of clinically relevant unwanted cardiovascular side-effects (tachycardia and major alterations in arterial blood pressure) is significant so medical bronchodilation may not be appropriate in pregnant sheep. 18 The anaesthetic management of the ewes in this study ensured that arterial blood pressure was measured and managed to maintain normotension. Uterine arteries have minimal autoregulation to maintain uterine perfusion pressure and uterine blood flow so it is essential to avoid maternal hypotension, minimize the duration of supine positioning and prevent frequent uterine contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In horses the risk of occurrence of clinically relevant unwanted cardiovascular side-effects (tachycardia and major alterations in arterial blood pressure) is significant so medical bronchodilation may not be appropriate in pregnant sheep. 18 The anaesthetic management of the ewes in this study ensured that arterial blood pressure was measured and managed to maintain normotension. Uterine arteries have minimal autoregulation to maintain uterine perfusion pressure and uterine blood flow so it is essential to avoid maternal hypotension, minimize the duration of supine positioning and prevent frequent uterine contractions.…”
Section: Discussionmentioning
confidence: 99%
“…In horses the risk of occurrence of clinically relevant unwanted cardiovascular side-effects (tachycardia and major alterations in arterial blood pressure) is significant so medical bronchodilation may not be appropriate in pregnant sheep. 18…”
Section: Discussionmentioning
confidence: 99%
“…20 While salbutamol is primarily a bronchodilator, the mechanism of action of this intervention is uncertain with variable results on improving PaO 2 reported in anaesthetised horses. 20,21 A study has shown increased heart rate and cardiac output after administration of salbutamol which might indicate a change in pulmonary perfusion besides putative bronchodilation. 22 Its application appears worth trying as undesirable effects are seldom and limited.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Pulmonary administration of nebulized salbutamol (β -adrenergic agonist) has been reported to reduce hypoxaemia. [20][21][22] In most cases, different modalities of mechanical ventilation are required to recruit lung areas where alveolar ventilation is insufficient. For example, the open lung concept (OLC) describes the application of high inspiratory pressure in combination with positive endexpiratory pressure (PEEP).…”
Section: Hypoxaemiamentioning
confidence: 99%
“…Hyponatremia can result from loss of sodium or gain of free water and it can occur in the presence of normovolaemia, dehydration or hypovolaemia. As a consequence of decreased serum sodium concentration, an osmotic gradient across the blood‐brain barrier could provoke the movement of free water into brain cells causing cerebral oedema 32 . The use of 3% saline has been described as a treatment approach for hyponatraemia 33 .…”
Section: Discussionmentioning
confidence: 99%